Clinical case of semilobar holoprosencephaly - A. V. Serezhkina; I. G. Khmelevskaya; N. S. Razinkova; T. A. Minenkova; I. I. Zhiznevskaya; A. S. Plekhanova (Лечащий Врач)
Since the direct etiological factors of developmental abnormalities are not known, the main groups of causes contributing to the formation of brain malformations are identified in the work. Great importance is given to the early diagnosis of malformations, which allows us to timely resolve the issue of the possibility of prolonging pregnancy, which is determined by the type of defect, compatibility with life and the prognosis for postnatal development. In the study of the considered malformation, such modern methods as prenatal ultrasound diagnostics, neurosonography, X-ray computer and magnetic resonance imaging of the brain, which have a sufficiently high informative value, play an important role. The terms of gestation are indicated, which make it possible to identify structural defects of the brain. Medical and genetic counseling helps to identify the risk of the appearance of sick offspring. The differential diagnosis of semilobar with other forms of holoprosencephaly was carried out. Possible clinical manifestations of the nosology under consideration are also noted. This article presents a clinical case of semilobar holoprosencephaly diagnosed in a boy at the age of 1 month. Upon admission, the mother complained of regurgitation and periodic anxiety of her son. The scope and results of the child's examination are set out below. Concomitant pathology was revealed in the form of an umbilical hernia, a congenital abnormality of the development of the urinary system: a horseshoe kidney; dropsy of the testicles and a cephalic form of hypospadias. After a course of maintenance therapy, the patient was discharged in a stable condition. Currently, there is no specific treatment for holoprosencephaly. Surgical interventions on the brain are rarely performed due to the severity of the patients ' condition, and therefore, the treatment of this pathology is possible only with the help of surgical correction of symptoms. Prolonged respiratory and cardiovascular dysfunction determines the fatal outcome of the disease.